2020
DOI: 10.1088/1361-665x/ab9e07
|View full text |Cite
|
Sign up to set email alerts
|

Shunted magnetostrictive devices in vibration control

Abstract: Structural vibrations in rotating machinery may lead to imprecise motion control, excessive noise, or even structural damage. Magnetostrictive materials can dissipate unwanted vibrations via hysteresis, eddy currents, and joule heating while exhibiting an electrically-tunable elastic modulus. Harnessing this feature, this article presents a shunted magnetostrictive device that includes an iron-gallium (Galfenol) rod, a permanent magnet array, a flux return path, and shunt circuits. The stiffness tunability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Denget al [83] later conducted a parametric study for a solidstate damper where the active component is a 6mm diameter and 10mm long Galfenol rod. The proposed damper was validated experimentally by Denget al [84], which demonstrated a maximum loss factor of 0.05 at 1kHz.…”
Section: Passive Controlmentioning
confidence: 98%
See 3 more Smart Citations
“…Denget al [83] later conducted a parametric study for a solidstate damper where the active component is a 6mm diameter and 10mm long Galfenol rod. The proposed damper was validated experimentally by Denget al [84], which demonstrated a maximum loss factor of 0.05 at 1kHz.…”
Section: Passive Controlmentioning
confidence: 98%
“…However, the bias magnetic field in this device was applied via an electromagnet requiring external power supply. Denget al [84] experimentally characterized the loss factor available from this shunted damper which was biased by permanent magnets. At 750Hz, the maximum loss factors from a Galfenol-based shunted damper are 0.06 and 1.34 for resistive shunt and capacitive shunt, respectively.…”
Section: Passive Controlmentioning
confidence: 99%
See 2 more Smart Citations